Elevated blood pressure positively associates with alpha-1 microglobulin in prepubescent children: the ExAMIN Youth SA study. Issue 1 (23rd January 2022) - Craig, Ashleigh; Gafane-Matemane, Lebo; Smith, Wayne; Mels, Carina; Uys, Lisa; Breet, Yolandi; Brits, Sanette; Mokwatsi, Gonste; Hanssen, Henner; Kruger, Ruan
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives and methods: Hypertension is a growing health concern in childhood populations and individuals of African descent. As the kidneys play a significant role in blood pressure regulation, we compared alpha-1 microglobulin (A1M) as a marker of proximal tubular function between young healthy black and white children ( n  = 957; aged: 5–9 years) and explored its association with blood pressure. Results: The black children had higher levels of A1M ( P  < 0.001) and higher DBP ( P  < 0.001) when compared with their white counterparts. In multiple regression analysis, SBP (adj. R 2  = 0.173, β = 0.151; P  < 0.001) and DBP (adj. R 2  = 0.110, β = 0.179; P  < 0.001) associated positively with A1M in the black children. In binary logistic regression, each standard deviation increase in A1M increased the odds of having elevated blood pressure by 28% ( P  = 0.002) in the black group, independent of age, sex, BMI z -score and body height. No significance was reached in the white children. Conclusion: Our findings highlight the importance of a marker of proximal tubular function, especially in children of black ethnicity, in the setting of elevated blood pressure. Early childhood screening for elevated blood pressure remains essential in order to promote primary prevention of hypertension and early onset kidney damage in children.